Analisis Perbandingan Kinerja Portofolio Saham Pada Kelompok Saham Kapitalisasi Besar Dan Kapitalisasi Kecil Di Bursa Efek Indonesia - Putri Sakina; Fathurrahman Anwar (Manajemen Inovasi Bisnis dan Strategi, 2023)
The purpose of this study is to find out how to compare the performance of the optimal portfolio of the large capitalization stock and small capitalization stock on the Indonesia Stock Exchange for the period January 2020 December 2022. This study uses the Single Index Model to form an optimal portfolio and the Sharpe Index to measure the performance of the formed portfolio. The population in this study were 45 stocks including large capitalization and 56 stock including small capitalization. The technique of determining the sample using purposive sampling, namely 19 shares in large capitalization and 29 shares in small capitalization. The observation method was used in this study for data collection. iThe result showed that during ithe period iJanuary 2020 December 2022 the performance of the ismall capitalization istock iportfolio with a iSharpe ivalue of 90,45% was ibetter than the performance of the ilarge capitalizationi stock iportfolio with a iSharpe ivalue 60,81%. This study is consistent with the size effect anomaly, where small capitalized stock perform better or provide higher returns compared to large capitalized stock.